Yield, Yield Components and Nutritional Traits Values of Biofortified Sorghum Hybrids in Mali - Maiga, Alfousseiny Mahamane; Nebie, Baloua; Diallo, Abdoulaye G.; Toure, Aboubacar; Danquah, Eric; Danquah, Agyemang (Journal of Agricultural Studies, 2022)
To assess the adaptation, yield potential, nutrient content and to identify the traits contributing directly and indirectly to yield increase, a two years’ study was conducted in four locations. Thus, a total of 28 F1 hybrids from two females and 14 male parents, were developed and used in this study along with the parents and four commercial hybrids. Seven (7) hybrids were identified with grain yield ranging from 4015 to 4624 kg-1ha; heading from 64 to 92 days; iron content from 8.63 to 91.15 ppm; Zinc content from 8.14 to 28.71 ppm; lysine content from 2.73 to 5.61 mg/100g; threonine content from 2.50 to 6.28 mg/100g. For both phenotypic and genotypic levels, a significant correlation on grain yield through plant height, panicle length, primary branch per panicle, grain number per panicle and number of whorls per panicle were found. Based on the path analysis, positive and significant direct and indirect effect of correlation were observed in this work for a cycle, grain quality, panicle length, primary branch per panicle, grain number per panicle and number of whorls per panicle at the phenotypic level.